2003
DOI: 10.2139/ssrn.487382
|View full text |Cite
|
Sign up to set email alerts
|

Female Labor Force Intermittency and Current Earnings: A Switching Regression Model with Unknown Sample Selection

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Certainly, highly educated women are more likely to marry highly educated men (Hotchkiss and Pitts 2005;Neal 2002;Herrnstein and Murray 1994) and would, therefore, likely feel more secure in leaving the labor market (with their husband's higher earning power and lower probability of unemployment). This suggests that interacting some of the regressors (e.g., education and marriage) may help take some of the explanatory power away from the intercept.…”
Section: E Which Behavior?mentioning
confidence: 99%
“…Certainly, highly educated women are more likely to marry highly educated men (Hotchkiss and Pitts 2005;Neal 2002;Herrnstein and Murray 1994) and would, therefore, likely feel more secure in leaving the labor market (with their husband's higher earning power and lower probability of unemployment). This suggests that interacting some of the regressors (e.g., education and marriage) may help take some of the explanatory power away from the intercept.…”
Section: E Which Behavior?mentioning
confidence: 99%
“…It is widely accepted that there is a penalty associated with intermittent labor force participation; workers who engage in intermittent activity earn lower wages than workers who do not (for example, see Hotchkiss and Pitts 2005, Baum 2002, Stratton 1995, and Jacobsen and Levin 1995. This penalty for intermittency is often offered as one source of the lower wages observed for women relative to men.…”
Section: The Role Of Labor Market Intermittency In Explaining Gender mentioning
confidence: 99%
“…Sorenson (1993) found that women with intermittent participation earned 34 percent less than women with continuous participation, after controlling for selection into intermittency as well as the labor force. Hotchkiss and Pitts (2005) construct an index for intermittent behavior that combines the number of periods of intermittency over a woman's work life, the amount of the work life spent in spells of intermittency, and the amount of time since the last spell of intermittency. They find that women are penalized at low levels of intermittency and women categorized as intermittent experience a penalty of roughly 16 percent.…”
Section: A Labor Market Intermittency and Lower Wagesmentioning
confidence: 99%
“…There is also evidence that women are penalized at fairly low levels of intermittent behavior (Hotchkiss and Pitts 2005) and that once a woman re-enters the labor market, she regains much of her lost earnings position, but that a small penalty persists for a relatively long period of time (Mincer andOfek 1982 andJacobsen andLevin 1995).…”
Section: Evidence Of Demand Factors In the Determination Of The Labormentioning
confidence: 99%